Arthroscopic Treatment of Intraosseous Ganglion Cysts of the Carpus - Teng, Xiao-Feng; He, Xin-Kun; Chen, Hong; Ruan, Jian (Frontiers in Surgery, 2022)
Objective: To investigate the application and the clinical efficacy of wrist arthroscopy in the treatment of carpal intraosseous ganglion cysts (IGCs). Methods: A retrospective case study method was adopted to analyze the clinical data of 28 patients with carpal IGCs admitted to the Sixth Hospital of Ningbo from April 2012 to January 2019. A hypodensity in the bone was shown by X-ray before the operation, with hypodensity and cystic change in the bone being confirmed by computed tomography and magnetic resonance imaging. Arthroscopic open window of the wrist, cystectomy, and autologous iliac bone graft implantation were conducted. Regular postoperative X-ray follow-ups were conducted to observe the healing after bone implantation. Patients were followed up regularly and assessed by the Modified Mayo Wrist Score in four aspects of the postoperative pain, wrist mobility, grip, and function to provide an objective overall assessment of the therapeutic outcome. Results: All 28 patients were followed up for 8 to 16 months, with an average follow-up duration of 10 months. After the operation, pain disappeared completely for 25 patients, and 3 cases showed significant improvement. All cases were pathologically confirmed as ganglion cysts and had first-stage bony healing after bone grafting with an average healing time of 10.8 weeks. The grip returned to normal for all patients, and wrist flexion and extension were the same as the healthy wrist for 25 patients, with a Modified Mayo Wrist Score of excellent in 19 cases and good in 9 cases. No recurrence was observed. Conclusion: In patients with symptomatic carpal IGCs, the application of arthroscopic open window, cystectomy, and autologous bone graft implantation could achieve satisfactory clinical therapeutic effects.